NiTiO3/NiFe2O4 nanocomposites: Simple sol–gel auto-combustion synthesis and characterization by utilizing onion extract as a novel fuel and green capping agent. (1st March 2016) - Ansari, Fatemeh; Bazarganipour, Mehdi; Salavati-Niasari, Masoud
Abstract: NiTiO3 /NiFe2 O4 nanocomposites were prepared via a simple sol–gel auto-combustion route using onion extract as a novel fuel and green capping agent. The present work focused on the synthesis and characterization of NiTiO3 /NiFe2 O4 nanocomposites for the first time. First, a sol of NiFe2 O4 was obtained, from metal nitrates and onion extract as reductant. Second, a sol of titanat was prepared by mixing of tetra-n-butyl orthotitanate, diethanolamin and ethanol. Then obtained sol was added to the NiFe2 O4 sol. The molar ratio of Ti to Ni had significant effect on morphology, magnetic properties, purity and phase of nanocomposites. Nanocomposites were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), cyclic voltammetry (CV) and vibrating sample magnetometer (VSM). The magnetic properties of the samples were also investigated using an alternating gradient force magnetometer where the optimum condition was performed in the molar ratio Ti/Ni 1:1. The photocatalytic activity of the synthesized products has been compared with the photodegradation activity of methyl orange (MO).